2022
DOI: 10.3390/ijms232315340
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Epstein-Barr Virus Minor Capsid Protein BORF1 by TRIM5α

Abstract: TRIM5α is a host anti-retroviral restriction factor that destroys human immunodeficiency virus (HIV) virions and triggers innate immune signaling. TRIM5α also mediates the autophagic degradation of target proteins via TRIMosome formation. We previously showed that TRIM5α promotes Epstein-Barr virus (EBV) Rta ubiquitination and attenuates EBV lytic progression. In this study, we sought to elucidate whether TRIM5α can interact with and induce the degradation of EBV capsid proteins. Glutathione S-transferase (GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…TRIM5α also induces the autophagic degradation of the target proteins. Lin et al showed that TRIM5α interacted with EBV capsid protein BORF1, and TRIM5α induced BORF1 ubiquitination [39]. Results suggest that TRIM5α destabilizes BORF1 via autophagic pathway.…”
mentioning
confidence: 99%
“…TRIM5α also induces the autophagic degradation of the target proteins. Lin et al showed that TRIM5α interacted with EBV capsid protein BORF1, and TRIM5α induced BORF1 ubiquitination [39]. Results suggest that TRIM5α destabilizes BORF1 via autophagic pathway.…”
mentioning
confidence: 99%